ENHANCING THE EFFECTIVENESS OF SCHOOL COUNSELING SERVICES THROUGH COUNSELING MEDIA: AN ACTION RESEARCH STUDY AMONG SCHOOL COUNSELORS AT SMAN 13 GARUT, INDONESIA - Herdiani Siti Aisyah; Agung Nugraha; Taofik Muhammad (PT Altin Riset Publishing, 2026)
This study examined the effectiveness of counseling media in improving school guidance and counseling services at SMAN 13 Garut, Indonesia. A school-based action research design was employed involving 20 students and two school counselors across a baseline assessment and two intervention cycles. The intervention integrated interactive presentations, short counseling videos, digital counseling information materials, electronic feedback forms, and interactive worksheets into counselor-led services. Data were collected using the Counseling Service Effectiveness Scale, observation sheets, student reflections, and counselor reflective journals. Quantitative data were analyzed using descriptive statistics, the Friedman test, repeated-measures analysis of variance, and effect-size estimation, while qualitative data were analyzed thematically and integrated with quantitative findings. The mean effectiveness score increased from 59.50 at baseline to 70.10 after Cycle I and 83.10 after Cycle II. The Friedman test indicated a significant difference across the three measurement points, χ²(2) = 40.00, p < .001. The repeated-measures ANOVA similarly demonstrated a significant change over time, F(2, 38) = 8,472.38, p < .001. Improvements were observed across accessibility, engagement, relevance, communication, service utilization, satisfaction, and perceived benefits, with student engagement showing the largest gain. The findings suggest that counseling media can strengthen school counseling services when systematically integrated with reflective, interactive, and counselor-led practices.